A luminal unfolding microneedle injector for oral delivery of macromolecules - Abramson, Alex (Nat Med, 2019)
Insulin and other injectable biologic drugs have transformed the treatment of patients suffering from diabetes. Patients and healthcare providers, however, prefer the oral route of administration, yet macromolecule drugs are not readily absorbed into the bloodstream through the gastrointestinal tract. We developed an ingestible capsule, termed the luminal unfolding microneedle injector (LUMI), which allows for the oral delivery of biologic drugs by rapidly propelling dissolvable drug-loaded microneedles into intestinal tissue using a set of unfolding arms. During ex vivo human and in vivo swine studies the device functioned safely and efficaciously. Using insulin as a model drug, we showed that after actuation the LUMI provided a faster pharmacokinetic uptake profile and a systemic uptake greater than 10% compared to subcutaneous injection over a 4 hour sampling period. With the ability to load a multitude of microneedle formulations, the device can serve as a platform technology to orally deliver therapeutic doses of macromolecule drugs.